Risk Management Plan: An Expert Analysis of Changes to the EAEU Good Pharmacovigilance Practice Requirements for the Content and Submission of the Document - T. M. Bukatina; E. V. Shubnikova (Безопасность и риск фармакотерапии)
The Council of the Eurasian Economic Commission published Decision No. 81 “On Amendments to the Rules of Good Pharmacovigilance Practice of the Eurasian Economic Union” on 19 June 2022 and enacted it on 6 December 2022. A risk management plan (RMP) is a key component of pharmacovigilance system documentation to be submitted in the marketing authorisation dossier for a medicinal product.The aim of the study was to review the changes to the requirements for the RMP structure, content, and submission from a regulatory expert’s perspective.Significant changes have been introduced to the requirements set by the regulatory authorities of the Eurasian Economic Union for RMPs for medicinal products. In particular, the requirements for the content of parts and modules of RMPs have been clarified and expanded. Furthermore, the amendments have introduced a new mandatory requirement that the information in parts and modules of the RMP and the dossier for a medicinal product should be consistent. Marketing authorisation holders have been provided with a detailed description of the conditions, procedures, and exceptional situations for submitting RMPs in dossiers. The updated requirements will help marketing authorisation holders improve and streamline their risk management processes.